2019
DOI: 10.1111/mmi.14413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the phosphoenolpyruvate:carbohydrate phosphotransferase system on toxin gene expression and virulence in Bacillus anthracis

Abstract: AtxA, the master virulence gene regulator of Bacillus anthracis, is a PRD-Containing Virulence Regulator(PCVR) as indicated by the crystal structure, posttranslational modifications and activity of the protein. PCVRs are transcriptional regulators, named for PTS Regulatory Domains (PRDs) subject to phosphorylation by the phosphoenolpyruvate phosphotransferase system (PEP-PTS) and for their impact on virulence gene expression. Here we present data from experiments employing physiological, genetic and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Bacteria depend on the phosphotransferase system (PTS) to sense and transport extracellular carbohydrates. The PTS has been also reported to affect virulence gene expression and infection in Streptococcus sp., Bacillus anthracis , and Vibrio cholerae ( 32 34 ), and mannose metabolites can also act as signaling molecules to coordinate virulence gene expression and influence infection ( 25 ). Surface components, including teichoic acids, a capsule, and enterococcal polysaccharide antigen, play key roles for Enterococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria depend on the phosphotransferase system (PTS) to sense and transport extracellular carbohydrates. The PTS has been also reported to affect virulence gene expression and infection in Streptococcus sp., Bacillus anthracis , and Vibrio cholerae ( 32 34 ), and mannose metabolites can also act as signaling molecules to coordinate virulence gene expression and influence infection ( 25 ). Surface components, including teichoic acids, a capsule, and enterococcal polysaccharide antigen, play key roles for Enterococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In B. anthracis, addition of glucose increased the expression of pagA in an AtxA-mediated manner and it was noted that this also required a functional CcpA (Chiang et al, 2011). Conversely, Bier and colleagues reported no such alterations in atxA expression in the presence of glucose in the media, nor were they able to detect a difference in atxA expression between a WT and ccpA deletion strain (Bier et al, 2020). Thus, changes in the availability of glucose could alter both AtxA and Mga expression through CCR rather than through direct interaction with EI/HPr/EIIB proteins.…”
Section: Catabolic Signals That Regulate Pcvrs the Impact Of Glucose On Pcvrsmentioning
confidence: 99%
“…Taken together, these reports suggest that AtxA activity may be directly linked to the PTS and phosphorylation. However, a recent report by Bier and colleagues has challenged the hypothesis that AtxA is directly phosphorylated by PTS proteins ( Bier et al., 2020 ). They found that EI and HPr did not directly phosphorylate AtxA in vitro , but instead, an intermediate regulatory protein is likely phosphorylated by the PTS which in turn modulates the expression of atxA .…”
Section: Prototypic Pcvrs In Pathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus anthracis, the bacterium that causes anthrax, is well known for its robust proliferation in diverse niches of mammalian hosts. Infection can result in up to 10 8 colony-forming units (CFU) per gram of tissue, including various organs, blood, and cerebral spinal fluid, at the time of host death (1)(2)(3)(4)(5). While the roles of several secreted virulence factors, including the anthrax toxin proteins, poly-D-glutamic acid capsule, siderophores, and proteases, have been discerned for anthrax (2,(6)(7)(8)(9), the metabolic attributes of B. anthracis that permit rapid proliferation to high numbers in multiple mammalian tissues have not been established.…”
Section: Introductionmentioning
confidence: 99%